Faktor Penyebab Remaja Mengakses Konten Pornografi dan Dampaknya terhadap Perilaku Berpacaran (Studi Kasus pada Remaja SMA di Kota Surabaya) - Amalia Dwi Ningtyas; Windhu Purnomo (Universitas Airlangga, 2023)
Background: Technological advances have negative and positive impacts on users, including teenagers. One of the most common negative impacts is accessing pornographic content. The availability of various applications that have various features is one of the reasons someone can more easily access pornographic content. Objectives: This study aims to determine various factors influencing high school teenagers in Surabaya to access pornographic content and its impacts on dating behavior. Methods: This study used a qualitative method with purposive sampling as a sampling technique. The study's data were obtained from in-depth interviews and documentation. Data analysis was carried out in three stages: (1) description, (2) interpretation, and (3) explanation. Result: The study's result indicates that various factors influence high school teenagers in Surabaya to access pornographic content. These factors include the use of smartphones from childhood or teenagers-hood without parental supervision, friends circle or social life both at school and outside of school, and high curiosity among teenagers, as well as the absence of parental education that can encourage the need for information on that education. The study's result also showed that teenagers who access pornographic content experience changes in their dating behavior. Conclusion: The conclusion in this study, there is a negative impact from the use of technology on high school youth in the city of Surabaya, namely accessing pornographic content. Accessing pornographic content also has an impact on how these teenagers date.